Dynamics of Illicit Arms Trade and Regional Security Challenges in West Africa: A Focus on Nigeria. - Balogun, Wasiu Abiodun (Africa Review, 2025)
This study investigates the interplay between illicit arms trade, transnational criminal networks and regional security in West Africa, with a particular focus on Nigeria. It examines the sources, drivers and actors involved, highlighting Nigeria's pivotal role as a source and transit point for illicit arms in the West African subregion. The research employs a mixed-methods approach, integrating qualitative and quantitative data for a comprehensive analysis. Thematic analysis of the data reveals the evolving tactics of transnational criminal networks, including their adaptation to countermeasures and their impact on local conflicts. Statistical methods further uncover previously underreported trends in arms trafficking routes. Notably, the study identifies a significant link between the influx of illicit arms and the intensification of sociopolitical instability in rural areas of Nigeria. The findings highlight the necessity for a multidimensional strategy that incorporates regional and international cooperation to dismantle these criminal networks and address the root causes of the illicit arms trade.